Dhikr Policy: Elite and Populism in Banda Aceh, Indonesia - Akmal, Saiful; Lhena Darwin, Rizkika; Nur Zalikha, Siti (International Journal of Psychosocial Rehabilitation, 2020)
Islamic populism trend is increasing in Indonesia. One of them is the dhikr policy in Aceh after the tsunami. Dhikr was and is used by elites both during the election as a campaign strategy as well as a populist policy in running the government in the city of Banda Aceh. This study uses a qualitative approach through in-depth and snowball interviews in the city of Banda Aceh. The results of this study explain three main findings. First, the dhikr policy is not just a ritual of worship; it merely serves an entertaining dhikr, which involves the government in terms of implementing and budgeting. Second, the motive of the political elite in the dhikras of a populist policy is to form an elite figure because it aims to display the symbol of faith, political compensation, means of communication, and public clarification. Finally, the zikr policy has not been able to solve the problems of individual and social welfare in Banda Aceh. Thus, increasing populism along with the birth of populist policies has formed an elite Indonesian figure(s) amidst the establishment of democracy today.